LOGISTICS PERFORMANCE FOR PRACTICE IN THE FMCG INDUSTRY THROUGH A SUPPLY CHAIN MANAGEMENT APPROACH - Umari Abdurrahim Abi Anwar; Aditia Wirayudha; Sri Suwarsi; Azyyati Anuar; Baderisang Mohamed (FEB Universitas Sam Ratulangi Manado, 2023)
Business competition that is getting tougher in the digitalization 5.0 era requires companies to further improve their business performance, especially in the aspect of supply chain management. Logistics, which is a critical process in supply chain management, needs to be made into an integrated system from upstream to downstream. Logistics activities which include distributing goods, managing warehousing, and managing consumer orders are of concern to the entire industry, including the FMCG industry. This study used a quantitative method using multiple regression analysis. The company used as a case study is a multinational FMCG company. Descriptive quantitative to describe a symptom, event, and incident that occurs when the attempt is made to photograph the events and incidents that are the center of attention of the researcher and then describe them as they are. This study focuses on logistics activities that become variables, namely transportation, handling and storage, and product availability. The results showed that transportation, handling and storage, and product availability. greatly affect the logistics performance of FMCG companies.